Utilization of Social Media as a Library Promotion Medium - Juairiah, Juairiah; Poppy, Poppy (Sharia Journal and Education Center Publishing, 2023)
Libraries as information centers have a responsibility to continuously innovate in providing services to thecommunity. This study aims to examine the utilization of social media as a promotional tool for libraries atthe Department of Library and Archives of Banjar Regency. This research employs field research with aqualitative research method. Data were collected through observation, structured interviews, anddocumentation techniques. Interviews were conducted with three informants from the social media division.The data sources consist of primary data obtained directly from informants through interviews andobservations, as well as secondary data in the form of documents relevant to this study. The results indicatethat the Department of Library and Archives of Banjar Regency has utilized various social media platforms,such as Instagram, TikTok, and Facebook, to disseminate service information and share literacy-relatedactivities. The implication of this study is that digital media can serve as an effective promotional tool toincrease library visits.